The influence of capital structure on Baltic corporate performance - Bistrova, Julia; Lace, Natalja; Peleckienė, Valentina (Journal of Business Economics and Management, 2011)
Seeking for the optimal capital structure lasts for more than 50 years and still is very topical, especially during the market turmoil as it happened in 2008. No perfect answer is yet provided to the question of how large debt amount should be kept on the accounts. The main objective of the present paper is to analyze the impact of capital structure decisions on the equity performance and on the profitability of the companies located in Baltics. The study covered the time period of 4 years (from 2007 till 2010) and the sample data of 36 “blue-chip” companies listed on the Baltic Stock exchanges. The results of the study discover positive relationship between stock performance and sufficiency of equity capital. Besides, there was found an inverse relationship between the level of debt and capital profitability confirming the pecking order theory that in the best case the company should use self-generated funds. Article in English. Kapitalo struktūra Baltijos įmonėse Santrauka. Optimalios kapitalo struktūros siekiama daugiau nei 50 metų ir tai vis dar yra labai aktualu, ypač per finansų krizę, įvykusią 2008 m. Kol kas nėra gauta galutinio atsakymo į klausimą – kokio dydžio skola turi būti laikoma sąskaitose. Pagrindinis šio straipsnio tikslas – išnagrinėti kapitalo struktūros sprendimų įtaką akcijų rinkai ir Baltijos šalių įmonių pelningumui. Tyrimas apėmė ketverių metų laikotarpį (nuo 2007 m. iki 2010 m.) ir 36 patikimiausių akcijų , blue chips“ duomenų, įtrauktų į Baltijos vertybinių popierių biržų sąrašus, pavyzdžius. Atlikus tyrimą nustatytas teigiamas ryšys tarp akcijų ir akcinio kapitalo pakankamumo. Be to, buvo nustatytas atvirkštinis ryšys tarp skolos lygio ir kapitalo pelningumo, patvirtinančio kapojimo kvotos teoriją, kad geriausiu atveju kompanija panaudos savo sukuriamus išteklius. Reikšminiai žodžiai: kapitalas, struktūra, atsipirkimas, rinka, lygis.